Appraisal of education as youth transformational agent for national development in Nigeria - Isaiah Ola ABOLARIN (African journal of social work, 2023)
The roles of youth in national development cannot be underestimated. The roles can be either negative, hampering the development or positive, enhancing the development. The kind of education received by the youth is a significant factor to whatever role they play in building a nation. Nigeria as a nation experiences a period of different violent and criminal behaviours among which are kidnaping for ransom, killing, internet crime (yahoo-yahoo), and money ritual killings and all these are going along with the global Covid-19 pandemic that also has negative impact on the national development. These behaviours are being majorly committed by the youth of the nation. This calls for transformation as a needed phenomenon for the youth in Nigeria using education as the tool, to build them for national development. Adopting desk research, the study was anchored on Omoluabi concept. The study concluded that since education is imperative for youth transformation, the educational stakeholders in Nigeria are to reform the education system that will lead youth to become acceptable adults thereby making positive contribution to the development of the nation. Journal website: https://ajsw.africasocialwork.net How to reference using ASWNet style: Abolarin, I. O. (2023). Appraisal of education as youth transformational agent for national development in Nigeria. African Journal of Social Work, 13(1), 22-29. https://dx.doi.org/10.4314/ajsw.v13i1.3